KAJIAN EKONOMI USAHATANI KUBIS DI KECAMATAN SUKAPURA KABUPATEN PROBOLINGGO - Ana Arifatus Sa’diyah; Rikawanto Eko Muljawan (Universitas Tribhuwana Tunggadewi, 2011)
Probolinggo Regency especially Sukapura is one of cabage production center area since this area is very suitable for cabage plants. Some problems are always faced by the farmers in that area was restrictiveness of capital such as wide of land, seeds, fertilizer, medicines, and employees. This research aimed to find out the productivity of cabage, factors affecting cabage production, income of farmer business entity of cabage, and efficiency of product ion cost at farmer business entity of cabage. The research method used was descriptive and correlation method, by determining the area purposively (purposive method). The method used to take the example was Disproportionate Stratified Random Sampling Method by stratum of area’s height. The data collection was done by using primary and secondary data. The data analysis used covered: (1) analysis of productivity index to know the productivity of cabage, (2) analysis of production function of Cobb-Douglas to know the factors affecting the cabage productivity, (3) analysis of income to know the profit of cabage farmers, and (4) analysis of R/C ratio to know the efficiency of production cost at farmer business entity of cabage. The research result done showed that: (1) the cabage productivity was 31,500 kg/ha; (2) the cabage productivity was affected by the wide of land, seeds, fertilizer, medicines, employees, and height of location, (3) the farmer business entity of cabage was profitable, and (4) the use of production cost at farmer business entity of cabage was efficient (R/C = 2,33)